Effects of disopyramide on electrophysiological properties of specialized conduction system in man and on accessory atrioventricular pathway in Wolff-Parkinson-White syndrome. Issue 8 (August 1975) - Spurrell, R A; Thorburn, C W; Camm, J; Sowton, E; Deuchar, D C
Abstract : Seven patients with normal specialized conduction system and three patients with the Wolff-Parkinson-White (WPW) syndrome were studied using programmed stimulation of the heart before and after the administration of intravenous disopyramide. The principal effect of this drug was to prolong the effective refractory period of the atria and ventricles, and to prolong the effective refractory period of the anomalous pathway in the WPW syndrome. In addition, it prolonged the conduction time in the anomalous pathway in the WPW syndrome. These findings suggest that disopyramide would be a useful and safe drug in the management of certain atrial and ventricular arrhythmias and in the management of the Wolff-Parkinson-White syndrome with atrial fibrillation.